Getting the Anthropocene so wrong. (August 2015) - Hamilton, Clive
Rather than clarifying it, a recent paper by Simon Lewis and Mark Maslin (2015), 'Defining the Anthropocene', adds to the confusion about the new epoch. The paper does not recognise that a paradigm shift has occurred, one in which environmental science has been displaced by Earth System science. The story tells of an Anthropocene beginning in 1610. It is not credible, as it is not based on an accurate understanding of the Earth System. In addition, in its determination to find a 'golden spike' the paper confuses stratigraphic markers for the epoch itself. It finds a marker when there is no event and ignores an event when it cannot find a marker.